VD_FINDINFO Faillite / 2025 / 23 vom 5. Mai 2025 - VD Tribunal cantonal (2025)
RESTITUTION DU DÉLAI, OUVERTURE DE LA FAILLITE, VOIE DE DROIT, INSOLVABILITÉ | 174 al. 1 LP, 174 al. 2 LP, 174 LP, 149 CPC (CH)